When the search domain is back region in Baltic: The Latvian aiz as compared to the Lithuanian už - Žilinskaitė-Šinkūnienė, Eglė; Šeškauskienė, Inesa (Vilnius University Open Series, 2021)
The paper sets out to examine prepositional polysemy in the Baltic languages. More precisely, the investigation focuses on the semantic structure of the Latvian preposition aiz + Gen. ‘behind, beyond’ as compared to the Lithuanian už + Gen. / Acc. ‘behind, beyond, for’ discussed in our previous paper (Šeškauskienė & Žilinskaitė-Šinkūnienė 2015). The methodology of research relies on the cognitive linguistic framework, mainly on the principle of motivated polysemy. Its key idea is that in the semantic network of the preposition all senses are seen as directly or indirectly linked to the central sense. In the case of aiz and už, the central sense encodes information about spatial configuration of Figure and Ground with the former located in the back region of the latter. A number of other senses, mostly concrete, derived from the central sense, overlap in Latvian and Lithuanian but demonstrate a differing degree of entrenchment. The most distinct differences are identifiable in the abstract senses.